SIKAP KERJA DENGAN KELUHAN MUSCULOSKELETAL DISORDERS (MSDS) PADA PEKERJA CIVIL DI PLTU (2X50 MW) TANJUNG KARANG, GORONTALO UTARA, GORONTALO - Muslimin B (Jurnal Kesehatan Yamasi Makassar, 2022)
Musculoskeletal complaints are complaints in the parts of the skeletal muscles that are felt by a person ranging from very mild complaints to very painful complaints. This complaint is triggered by various factors, one of which is work factors such as excessive muscle stretching, unnatural work postures, repetitive movements, and environmental factors such as vibration, pressure and microclimate. The purpose of the study was to determine the relationship between work attitudes and complaints of musculoskeletal disorders (MSDs) in civil workers at PLTU 2x50mw, Tanjung Karang, North Gorontalo. Methods: This research is an analytical observational study using a cross sectional approach using a questionnaire sheet and an REBA ( Rapid Entire Body Assessment ) observation sheet. The sample taken in this study amounted to 86 people from 112 population of civil workers at PLTU 2X50MW Tanjung Karang, North Gorontalo using the Proportional Random Sampling technique . The results of the study of sitting posture with complaints of musculoskeletal disorders with the chi-square test obtained a value of p = 0.715 (p <0.05), this means that H0 is accepted and Ha is rejected, standing postures with complaints of musculoskeletal disorders and slouching attitude with complaints of musculoskeletal disorders using the test chi-square value obtained p = 0.000 (p <0.05), this means that H 0 is rejected and Ha is accepted. The conclusion of sitting posture with complaints of musculoskeletal disorders can be interpreted that there is no relationship, standing posture with complaints of musculoskeletal disorders can be interpreted as having a relationship . The results of the analysis of bending attitude with complaints of musculoskeletal disorders . can be interpreted that there is a relationship